2017
DOI: 10.21829/myb.2017.2311534
|View full text |Cite
|
Sign up to set email alerts
|

Variation in wood physical properties within stems of Guazuma crinita, a timber tree species in the Peruvian Amazon

Abstract: An understanding of wood physical properties and the interrelationships that govern them is required for efficient utilization of timber tree species. Guazuma crinita is a fast-growing timber tree of agroforestry systems in the Peruvian Amazon. The aim of this study was to assess variation in wood physical properties within the G. crinita stem. Wood samples were obtained from the base, middle and top of the stem of 12 randomly selected eight-year-old trees from six provenances in order to determine wood moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…Therefore, the density cannot be used as a predictor of the T / R ratio for the three tested genera. The results were in agreement with (Tuisima-Coral et al, 2017) who found insignificant correlation between T/R ratio and basic density and specific gravity of Guazuma crinite wood. In contrast, (Van Duong and Matsumura, 2018) found linear positive correlation between T/R ratio and basic density of Melia azedarach wood.…”
Section: Figure 1 Relationship Between Density and T/r Ratiosupporting
confidence: 92%
“…Therefore, the density cannot be used as a predictor of the T / R ratio for the three tested genera. The results were in agreement with (Tuisima-Coral et al, 2017) who found insignificant correlation between T/R ratio and basic density and specific gravity of Guazuma crinite wood. In contrast, (Van Duong and Matsumura, 2018) found linear positive correlation between T/R ratio and basic density of Melia azedarach wood.…”
Section: Figure 1 Relationship Between Density and T/r Ratiosupporting
confidence: 92%
“…A madeira é um material de grande potencial de uso na construção civil e pode ser procedente de florestas naturais ou plantadas (MAZURANA et al, 2011;MATOS et al, 2012;TER STEEGE et al, 2016;TUISIMA-CORAL et al, 2017). Entre os materiais comumente utilizados, a madeira é o único renovável, expressa elevada relação entre a resistência e o peso, e sua produção gera poucos impactos ambientais.…”
Section: Introductionunclassified
“…Wood is a natural raw material obtained from natural or planted forests (MAZURANA et al, 2011;MATOS et al, 2012;TER STEEGE et al, 2016;TUISIMA-CORAL et al, 2017). In Brazil, Eucalyptus tree genus are utilized for a variety of applications, among them: pulp and paper, charcoal, essential oils, boards, firewood, construction, and furniture (GUIMARÃES JUNIOR et al, 2009BRITO;PERRÉ, 2010;IWAKIRI et al, 2013;SOARES et al, 2015;MATTOS et al, 2014;NEIVA et al, 2015;BALLESTEROS et al, 2015).…”
Section: Introductionmentioning
confidence: 99%